Analisis Kepatuhan Akad Baku Peer to Peer Lending Syariah terhadap Fatwa DSN MUI Nomor 117 DSN-MUI/II/2018 (Studi Kasus pada PT. Qazwa Mitra Hasanah) - Muh Rizwan Azzahidi; Nurmu’izzatin Zaharatul Parhi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The purpose of this study is to understand the synchronization of the standard contracts contained in Qazwa.id with Islamic law and to find out how the legal protection for financiers is in the standard contracts made by Qazwa. This research uses the literature study method with DSN-MUI fatwa data sources, laws, POJK and articles that are relevant to this research. The results of this study are that overall Qazwa's standard contracts and the general terms and conditions that apply to Qazwa are in accordance with DSN MUI Fatwa Number 117 of 2018 concerning Information Technology-Based Financing Services Based on sharia principles. Legal protection for consumers in the early stages or before the contract takes place, consumers will receive education about platform, information and product transparency services. Qazwa also provides online customer service that responds swiftly to questions and complaints from potential lenders. Therefore, the form of legal protection for consumers in the early stages before the contract has been implemented and implemented optimally by the organizers.